THE EFFECT OF COOPERATIVE LEARNING THEORY ON THE TEACHING OF TRIGONOMETRY AT HIGH SCHOOLS - Asomah , Richard Kyere; Assamah, Gabriel; Narh-Kert, Millicent; Nusrat Manu, Harriette; Agyei, Emmanuel (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
The benefits of enacting lessons anchored on Cooperative learning (CL) in mathematics has been well documented. However, in particular, the effect of CL on the teaching of trigonometry is rare at the second cycled educational institutions. This study, therefore, is aimed at exploring the efficacy of CL in enhancing meaningful teaching and learning of trigonometry at the Senior High School (SHS) in Ghana. Mixed method research design was employed to collect data using a questionnaire with both close-ended and open-ended items, and trigonometric achievement tests with essay type questions. A stratified sampling approach was used to select 55 students as the participants in the study. Descriptive statistics, paired sample t-test and thematic coding were used in analysing the data. The findings showed that, there were significant improvement in the students’ learning outcomes in trigonometry. In particular, the study revealed improved performance in students’ pre-test and post-test scores after participating in CL lessons. Finally, the students’ overall positive dispositions towards the CL-lessons were reflected in high means scores on the subscales: -Positive interdependence, Individual accountability, Face-to-face promotive interaction, Social skills and Group processing, depicting favourable experiences with the CL-lessons. To this end, the authors argue that, to develop higher order thinking skills in students the use of CL in the teaching and learning of trigonometry ought to be prioritised. It is recommended that; management of educational institution should consider conducting professional development training for educators who desire CL as a means of instruction. Implications for policy and further research are discussed.